2022
DOI: 10.3390/pharmaceutics14102001
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of Drug Transporters, Rather Than Metabolizing Enzymes, Conditions the Pharmacokinetics of Rasagiline

Abstract: Rasagiline is a selective and irreversible inhibitor of monoamine oxidase type B with neuroprotective effect, indicated for the management of Parkinson’s disease. The aim of this work was to evaluate the impact of seven CYP1A2 alleles and of 120 additional variants located in other CYP enzymes (e.g., CYP2C19), UGT enzymes (e.g., UGT1A1) or other enzymes (e.g., NAT2), and transporters (e.g., SLCO1B1) on the pharmacokinetic variability and safety of rasagiline. A total of 118 healthy volunteers enrolled in four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
(35 reference statements)
1
4
0
Order By: Relevance
“…Finally, one study with a more in vitro methodology was accepted for publication, evaluating the impact of genetic variants and mRNA on CYP1A2 function. Consistent with our association study with rasagiline [ 13 ], CYP1A2 variants showed no relationship with CYP1A2 activity. This shows that the current definition of CYP1A2 alleles is probably incorrect, and that priority should be given to the structural characterization of this gene.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Finally, one study with a more in vitro methodology was accepted for publication, evaluating the impact of genetic variants and mRNA on CYP1A2 function. Consistent with our association study with rasagiline [ 13 ], CYP1A2 variants showed no relationship with CYP1A2 activity. This shows that the current definition of CYP1A2 alleles is probably incorrect, and that priority should be given to the structural characterization of this gene.…”
supporting
confidence: 90%
“…Four works were accepted concerning neurodegenerative and neurodevelopmental disorders. Starting with the first type of disorders, ABCB1 rs1045642, ABCC2 rs2273697, and SLC22A1 rs34059508 were related to variability in the exposure to rasagiline, a drug used for the management of patients with Parkinson’s disease (PD) [ 13 ]. To date, no pharmacogenetic biomarker has been proposed for rasagiline or any other drug prescribed for the treatment of this disease.…”
mentioning
confidence: 99%
“…Every studied gene has already been related to methotrexate [7–9] so our descriptive study propose analyzing the genotype‐informed pharmacogenetic phenotype is a good alternative to in vitro assays to establish new gene‐enzyme interactions, particularly for old drugs like methotrexate, as previous studies of this group suggest [33, 34].…”
Section: Discussionmentioning
confidence: 99%
“…The formulation was let to flow through a membrane filter with a 0.20 m pore size that was retained on a mesh plate. Readings were recorded in triplicate [27,28]. The % deformability was calculated by the following equation:…”
Section: % Deformability Indexmentioning
confidence: 99%